Efektivitas Berbagai Dosis Vermikompos terhadap Pertumbuhan Bibit Kakao (Theobroma cacao L.): Effectiveness of Different Vermicompost Application Rates on the Growth of Cocoa (Theobroma cacao L.) Seedlings - Syofiani, Riza; Giska Oktabriana (DINAMIKA PERTANIAN, 2026)
Background:Indonesia’s cocoa production has declined over the past two years, despite the highly promising market potential for cocoa. One strategy to enhance the growth of cocoa seedlings is through the improvement of planting media by incorporating organic amendments such as vermicompost. Objective: This study aimed to (1) evaluate the effectiveness of different vermicompost application rates on the growth of cocoa seedlings (Theobroma cacao L.), and (2) determine the optimal vermicompost rate for cocoa seedlings. Methods:The experiment was conducted over a four-month period at the experimental field of the Politeknik Pertanian Negeri Payakumbuh, employing a Completely Randomized Design (CRD) with six levels of vermicompost application rates: 0, 25, 50, 75, 100, and 125 g plant⁻¹, each treatment replicated four times. Observations included soil parameters (total nitrogen, available phosphorus, organic carbon, and soil pH) and plant growth parameters (plant height, number of leaves, stem diameter, shoot dry weight, and root dry weight). Data were analyzed using ANOVA at a 5% significance level, followed by LSD test. Results:Vermicompost application significantly affected plant height, leaf number, stem diameter, shoot dry weight, and root dry weight. The application rate of 125 g plant⁻¹ resulted in the most optimal growth, with plant height of 22.78 cm, 16.13 leaves, shoot dry weight of 2.99 g, and root dry weight of 1.70 g. These improvements were associated with enhanced soil chemical properties, particularly increased total nitrogen, available phosphorus, organic carbon, and soil pH Conclusions:Vermicompost at a dose of 125 g plant⁻¹ is effective in improving the growth of cocoa seedlings and soil chemical properties, and is recommended as an optimal organic amendment for cocoa nursery.